USO DE DOS ESPECIES DE MACRÓFITAS ACUÁTICAS, Limnobium laevigatum Y Eichhornia crassipes PARA EL TRATAMIENTO DE AGUAS RESIDUALES AGRO INDUSTRIALES - Valderrama Valderrama, Luz Teresa; Programa de Saneamiento y Biotecnología Ambiental, Departamento de Biología, Facultad Ciencias, Pontificia Universidad Javeriana, Bogotá (Pontificia Universidad Javeriana, 2013)
The effect oftwo aquatic macrophytes (Limnobíwn laevigatum and Eichhomía crassípes) was evaluated on a pilot-scale basis in order to improve an agroindustrial wastewater effluent treatrnent. These species were found to be use fui in stabilizing and neutralizing wastewater pH and depleting total coliforrns, DBO, DQO and total suspended solids concentrations. The removal efficiencies were: total coliforrns, 68 and 22% with L. laevigatum and E. crassípes respectively; DBO, 76 and 53%; DQO, 26 and 18% and TSS, 70 and 56% with L laevigatum andE. crassipes respectively. L. laevigatum produced a increase in total alcalinity in respect to the affluent and was more efficient in fecal coliforrns removal than E. crassipes. No changes on temperature, conductivity, dissolved solids or chloride were obtained for any system in respect to the affluent.